La Organización Comunitaria para el Desarrollo Social en el Barrio los Huilcos de la Parroquia Rural Vilcabamba desde la intervención del Trabajador Social - Tapia Soria, Lizbeth Estefania (2018)
The present research work is called "THE COMMUNITY ORGANIZATION FOR SOCIAL DEVELOPMENT IN THE NEIGHBORHOOD OF THE RURAL PARLIAMENT VILCABAMBA SINCE THE INTERVENTION OF SOCIAL WORKERS" whose livelihood is focused on the little organization generated by the poor leadership caused by the Neighborhood directive. The work is supported by the application of 136 surveys to the residents, among adolescents, youth, adults and seniors, including 4 people belonging to the Los Huilcos neighborhood committee.The specific objectives allowed for the adequate management of theories, through the in-depth analysis of each of the variables studied, in addition to determining causes and effects, which in a way enabled a direct contact with the investigated reality, thus allowing the development of strategies and alternative solutions. For the development of the present investigation, the methodology of community self-development was used, focused on the first three stages, initial exchange with the subject in need of professional action, whose purpose was to know the general perception of the complainant about their main discomforts, demands and Needs that require timely attention, according to the exploration of the scenario, which makes it possible to capture empirical data related to the latent problem, which in turn makes it possible to confront with theoretical referents of departure, finally with the diagnosis and search for solutions, spaces of reflection were created that Promoted the transformative force, here the involved subjects granted alternative solutions that were evidenced with the support of investigative techniques and tools such as the observation sheet, field notebook and surveys. 5 Among the main findings is the deficient leadership that totally influences the organization and community development of Barrio los Huilcos, whose causes are reflected in the lack of interest and lack of time, which the neighborhood committee notes when it comes to assuming its responsibilities, This criticism was corroborated by the same managers, the lack of training in the management of strategies to direct and organize the inhabitants, the lack of initiative to generate innovative ideas, poor interpersonal relations maintained by the inhabitants, the lack of concern in meeting the needs Economic and social problems, all of which have generated important consequences such as the low participation and interaction of the residents, mainly the little social development of the Los Huilcos neighborhood that translates into the use of social change based on projects and initiatives that conquer the Community space. An initiative to improve the community organization for the social development of the Barrio los Huilcos was born from the same inhabitants, by means of integration into meetings where all are participants in the decisions that are established, training of young leaders trained and those who promote a true social change whose Ideas are centered on the innovation and social integration of the inhabitants of the sector. From the results obtained, the initiative was born to create and design a social action proposal aimed at strengthening community leadership and organization, through workshops related to leadership and entrepreneurship training, recreational and interactive activities.